2022
DOI: 10.1021/acschemneuro.1c00761
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxynorketamine Pharmacokinetics and Antidepressant Behavioral Effects of (2,6)- and (5R)-Methyl-(2R,6R)-hydroxynorketamines

Abstract: (R,S)-Ketamine is rapidly metabolized to form a range of metabolites in vivo, including 12 unique hydroxynorketamines (HNKs) that are distinguished by a cyclohexyl ring hydroxylation at the 4, 5, or 6 position. While both (2R,6R)- and (2S,6S)-HNK readily penetrate the brain and exert rapid antidepressant-like actions in preclinical tests following peripheral administration, the pharmacokinetic profiles and pharmacodynamic actions of 10 other HNKs have not been examined. We assessed the pharmacokinetic profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…More (2S,6S)-6HNK than (2R,6R)-6HNK was formed. The same was found previously in mice [8]. In human plasma collected after treatment with KET and then analyzed with an achiral LC-MS method, 6HNK was described in the literature as the major circulating metabolite ((2S,6R); (2R,6S)-6HNK > (2S,6S); (2R,6R)-6HNK) followed by (2S,5S); (2R,5R)-5HNK, (2S,4R); (2R,4S)-4HNK, (2S,4S); (2R,4R)-4HNK, and (2S,5R); (2R,5S)-5HNK.…”
Section: Analysis Of Hnk Stereoisomerssupporting
confidence: 90%
See 1 more Smart Citation
“…More (2S,6S)-6HNK than (2R,6R)-6HNK was formed. The same was found previously in mice [8]. In human plasma collected after treatment with KET and then analyzed with an achiral LC-MS method, 6HNK was described in the literature as the major circulating metabolite ((2S,6R); (2R,6S)-6HNK > (2S,6S); (2R,6R)-6HNK) followed by (2S,5S); (2R,5R)-5HNK, (2S,4R); (2R,4S)-4HNK, (2S,4S); (2R,4R)-4HNK, and (2S,5R); (2R,5S)-5HNK.…”
Section: Analysis Of Hnk Stereoisomerssupporting
confidence: 90%
“…Hydroxynorketamine (HNK) stereoisomers are metabolites of KET and have become a focus of interest for drug repurposing, as they have shown strong antidepressant effects, whereas typical side effects known from the treatment with KET, such as dissociation and substance abuse, were absent [4,8,9]. Preclinical studies have revealed the (2R,6R)-6HNK enantiomer as having the strongest antidepressant effect followed by (2S,6R)-6HNK, (2R,6S)-6HNK, and (2S,6S)-6HNK [8]. These enantiomers arise when KET is stereoselectively metabolized by cytochrome P450 enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…However, Zanos’ hypothesis has been questioned as many researchers believe that the NMDA receptor blockage is involved in the antidepressant effects of ketamine and its metabolites 31 . Interestingly, a recent preclinical study in mice suggested that the potency of the HNKs is associated with the conformation of the cyclohexanone ring system in the (2, 6)‐HNKs 82 . However, the therapeutic antidepressant potential of (2, 6)‐HNK observed in preclinical studies has not been evaluated in a prospective clinical study.…”
Section: Activity Of Ketamine Metabolitesmentioning
confidence: 99%
“…31 Interestingly, a recent preclinical study in mice suggested that the potency of the HNKs is associated with the conformation of the cyclohexanone ring system in the (2, 6)-HNKs. 82 However, the therapeutic antidepressant potential of (2, 6)-HNK observed in preclinical studies has not been evaluated in a prospective clinical study.…”
Section: Activity Of Ketamine Metabolitesmentioning
confidence: 99%
“…Gould's team has identified one such molecule, called (2R,6R)-hydroxynorketamine. In animal studies 5 , the metabolite can produce ketamine-like antidepressant effects all on its own, but without inducing the dizzying high that causes some people to misuse ketamine. Gould and his colleagues have launched a phase I trial of the metabolite in healthy volunteers, and hope to begin phase II studies in treatment-resistant depression in the coming year.…”
Section: Astonishing Anaestheticmentioning
confidence: 99%